2018
DOI: 10.1073/pnas.1804233115
|View full text |Cite
|
Sign up to set email alerts
|

MYB30 links ROS signaling, root cell elongation, and plant immune responses

Abstract: Reactive oxygen species (ROS) are known to be important signal molecules that are involved in biotic and abiotic stress responses as well as in growth regulation. However, the molecular mechanisms by which ROS act as a growth regulator, as well as how ROS-dependent growth regulation relates to its roles in stress responses, are not well understood. We performed a time-course microarray analysis of root tips upon treatment with hydrogen peroxide, which we named "ROS-map." Using the ROS-map, we identified an MYB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 50 publications
4
116
0
Order By: Relevance
“…We examined changes in the expression levels of these four genes in Col-0 and myb30 roots exposed to control and 5 µM ABA treatments for 24 h using RT-qPCR (Figure 4(a)). All four genes were strongly downregulated in myb30 roots, which was consistent with our previous results [13]. Furthermore, LTP5 and LTPG1 but not LTPG2 and PME44 were significantly upregulated by ABA treatment in Col-0 roots.…”
Section: Myb30-regulated Genes Were Involved In Controlling Root Cellsupporting
confidence: 92%
See 4 more Smart Citations
“…We examined changes in the expression levels of these four genes in Col-0 and myb30 roots exposed to control and 5 µM ABA treatments for 24 h using RT-qPCR (Figure 4(a)). All four genes were strongly downregulated in myb30 roots, which was consistent with our previous results [13]. Furthermore, LTP5 and LTPG1 but not LTPG2 and PME44 were significantly upregulated by ABA treatment in Col-0 roots.…”
Section: Myb30-regulated Genes Were Involved In Controlling Root Cellsupporting
confidence: 92%
“…We previously reported that MYB30 has important functions as a root growth regulator under ROS signaling [13]. During the analysis of MYB30 function, we also found that it seems to act independently of plant hormone signals such as auxin and cytokinin.…”
Section: Interaction Between Myb30 and Plant Hormones In Root Growthmentioning
confidence: 73%
See 3 more Smart Citations